2015
DOI: 10.3109/01443615.2015.1030604
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in lipid peroxidation and T-cell function in women with hyperemesis gravidarum

Abstract: The objective of this study was to investigate serum adenosine deaminase (ADA) activity as a marker of T lymphocyte activation and parameters of oxidative stress and antioxidant defence in hyperemesis gravidarum (HG). Serum ADA activity, malondialdehyde (MDA), catalase (CAT) and glutathione peroxidase (GPx) levels were investigated in 40 pregnant women with the HG and 40 with healthy pregnancies, in a descriptive study. Although serum ADA and CAT were measured to be higher in HG group, the difference was not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…Güney et al [24] found that CAT was significantly lower in HG and attributed to the deficiency of antioxidants taken with nutrients. However, Biberoğlu et al [23] found that the CAT level was high, although this was not significant. We found that CAT levels were significantly higher in our study.…”
Section: Groupsmentioning
confidence: 92%
See 1 more Smart Citation
“…Güney et al [24] found that CAT was significantly lower in HG and attributed to the deficiency of antioxidants taken with nutrients. However, Biberoğlu et al [23] found that the CAT level was high, although this was not significant. We found that CAT levels were significantly higher in our study.…”
Section: Groupsmentioning
confidence: 92%
“…Although the exact mechanism is not known, lymphocytes or monocytes are thought to play an essential role in serum ADA activity [21,22]. In the study by Biberoğlu et al [23], although the serum ADA and CAT levels were higher in the HG group, the differences were not significant. There is no previous study of MPO in HG patients, this will be the first study.…”
Section: Groupsmentioning
confidence: 94%
“…choosing a bland diet, increasing carbohydrate intake, decreasing fat intake, avoiding offensive food odors, and also avoiding iron supplementation, if possible are recommended. till the nausea resolves, Omitting prenatal vitamins containing iron may be useful (16).…”
Section: Intervention Strategies For Treatment Of Hyperemesis Gravidarummentioning
confidence: 99%
“…Hiperemezis gravidarum (HEG) gebelik boyunca gerçekleşen tüm hospitalizasyonların 1/3'ünden sorumlu olan ve sıklıkla sıvı-elektrolit bozukluğu ve asit-baz dengesizliğine sebep olan klinik bir durumdur (1). Her ne kadar tüm gebeliklerin %70 ile %80'i arasında görülebilen gebeliğe bağlı bulantı ve kusmalar klinik olarak HEG ile benzer özellikler göstermekte ise de, HEG'de klinik tabloya sıklıkla kilo kaybı, idrarda keton pozitifliği ve dehidratasyon gibi tablolar da eşlik etmektedir (2).…”
Section: Introductionunclassified
“…Düşük glutatyon seviyesi HEG'deki oksidatif stresin bir kanıtı olarak değerlendirilmiştir. Buna benzer şekilde HEG'de artmış oksidatif stres kanıtları gün geçtikçe artarak devam etmiş, ancak bunun aksini gösteren çalışmalar da literatürde kendine yer bulabilmiştir (1,7,9). Tüm bu bulgular birlikte değerlendirildiğinde HEG patogenezinde oksidatif stresin rolünü net bir şekilde söylemek halen mümkün değildir.…”
Section: Introductionunclassified